Analisis Musikal dan Non-Musikal pada Perjamuan Kudus Gereja Advent Bandar Lampung - Debora Trefy Nicolaas; Erizal Barnawi; Bian Pamungkas (Universitas Negeri Medan, 2025)
The Holy Communion is held as a reminder of Jesus' death on the Cross to redeem humans from sin. This study uses a descriptive qualitative method to determine the Musical and Non-Musical Analysis found in the Holy Communion at the Bukit Kemiling Permai Adventist Church. Data were received through observation, interviews, and documentation and processed using musical and non-musical analysis theories. The Holy Communion song